Metacognition – Strategy Use and Metacognitive Knowledge – in EFL Listening: A Pilot Study - Tasnima Aktar (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2020)
Metacognition, the term invented by Flavell (1979), has the potential to facilitate language learning and listening (Flavell, 1979; Vandegrift and Goh, 2012; Wenden, 1991). However, little has been known about holistic metacognition in L2 listening and in an ‘input-poor’ EFL context of Bangladesh. This pilot study aims to explore metacognition of tertiary level students in an EFL context of Bangladesh. A pilot study was conducted to trial four data collection instruments as part of the author’s PhD research; however, this study reported pilot data collected via the three tools only. Listening Strategy Questionnaire (LSQ) was exploited to collect quantitative data on off-line, perceived strategy use and a Listening Test adapted from IELTS listening was used to assess learners’ listening comprehension. Semi-structured Interview elicited qualitative data on students’ perceptions of EFL listening i.e., metacognitive knowledge. The results of this pilot study revealed moderate use (M=3.55) of overall strategy among the participants, and highest use (M=3.69) of the category of metacognitive strategy. Among individual strategies, directed attention (a metacognitive strategy) was used most frequently (M=4.22) and grouping (a cognitive strategy) was used least frequently (M=2.88). The results of Pearson correlations between students’ listening comprehension and strategy use showed significant positive correlation with planning (.309*) and substitution (.274*) strategies but significant negative correlations with linguistic inferencing (-.343*) and note-taking (-.281*) strategies. Thematic analysis of perception data of two representative samples revealed their awareness of a great number of aspects of Metacognitive Knowledge and showed considerable differences between the less successful listener (LSL) and the more successful listener (MSL) on their metacognitive knowledge, particularly in strategy knowledge. This study has pedagogical implications for raising awareness about metacognition among EFL listeners. Key words: metacognition, metacognitive knowledge, strategy use, tertiary level, EFL listening